1998
DOI: 10.1302/0301-620x.80b5.8540
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral recurrent lumbar disc herniation

Abstract: We analysed prospectively 26 patients who had revision operations for ipsilateral recurrent radicular pain after a period of pain relief of more than six months following primary discectomy. They were assessed before the initial operation, between the two procedures and at a minimum of two years after reoperation. MRI was performed before primary discectomy and reoperation. Fifty consecutive patients who had a disc excision during the study period but did not have recurrent radicular pain, were analysed as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
140
2
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(164 citation statements)
references
References 0 publications
12
140
2
10
Order By: Relevance
“…None of the patients had a poor result, although three patients had transient neurological deficits, which were completely resolved within 3 months. These are comparable with the rates of satisfactory clinical results reported by others [2,3,12,15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…None of the patients had a poor result, although three patients had transient neurological deficits, which were completely resolved within 3 months. These are comparable with the rates of satisfactory clinical results reported by others [2,3,12,15].…”
Section: Discussionsupporting
confidence: 91%
“…Recurrent lumbar disc herniation (RLDH) is a major cause of surgical failure, the incidence of which is reported from 5 to 11%, with an increased incidence as the follow-up period is extended [2,5,13]. The optimal technique for treating RLDH is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ayman A. El Shazlyand colleagues (6) reported that patient outcomes following reoperative discectomy were satisfactory and similar to those in patients treated with primary disc excision. Cinotti and colleagues (7) reported an overall good outcome rate of 85% and a return-to work rate of 81% among 26 patients who had undergone reoperative discectomy. Ozgen and colleagues (8) performed reoperative decompressions in 114 patients including reoperative discectomies in 89 patients with a recurrent disc herniation.…”
Section: Discussionmentioning
confidence: 98%
“…Cinotti et al 3 prospectively compared outcomes obtained in 26 patients who had undergone revision discectomy with outcomes in 50 control patients who had undergone a primary discectomy. They found no significant difference between groups; postoperative satisfaction was reported by 85% of those in the revision group and 88% in the control primary discectomy group.…”
Section: Discussionmentioning
confidence: 99%